STRATEGI PENGEMBANGAN CABAI KERITING DI KECAMATAN MODAYAG KABUPATEN BOLAANG MONGONDOW TIMUR - Novia Cristi Lumika; Oktavianus ., Porajouw; Melissa L.G. Tarore (Sam Ratulangi University, 2017)
The purpose of this study is to describe the development strategy of curly pepper. The research conducted for 3 months from April to June 2017. The research sites were in three villages in Modayag Sub-district, East Bolaang Mongondow District, in Purworejo, Purworejo Timur and Sumber Rejo villages. This study used primary data and secondary data. Primary data obtained from observation and direct interview with respondent based on questionnaire. Secondary data collected and obtained from Agriculture Department, Implementation Agency for extension of farming, fishery and forestry (BP4K), BPS-Statistics of East Bolaang Mongondow, Traders / Entrepreneurs, Modayag District Offices and Village Offices in Villages Purworejo, Purworejo Timur and Sumber Rejo. Sampling method using purposive sampling method, as many as 15 samples from the total population in three villages. Samples taken are the curly chili farmers that produce in 2016. Descriptive data analysis and, using analysis of Strengths, Weakness, Opportunities and Threats (SWOT). Based on the result of the research, it can concluded that the alternative strategy of Strength Opportunity (SO) as follows: Utilization of education and experience and skills of farmers in producing quality production and superior in the market and can meet consumer needs and demand. Establish good relationships between farmers and agricultural institutions, in order to sustain the successful development of agriculture and farming. With the development of increasingly modern technology, and the utilization of facilities and infrastructure that allows to obtain optimal results. The need for agricultural products never changes according to their development; the price must always adjusted to market conditions.